Pendidikan Agama Kristen Sebagai Pendekatan Dalam Pembentukan Karakter Siswa SMA Kristen Nehemia Galela Di Era Digital - Tasiringan, Marton; Hohakay, Ilona Ervvina (Didache: Jurnal Teologi dan Pendidikan Kristen, 2025)
The purpose of this study is to analyze the character formation of students at Nehemia Galela Christian High School, and analyze Christian Religious Education as an Approach in character formation of students at Nehemia Galela Christian High School digitally so that students have Christian characters namely intelligent, caring, dignified, spiritually disciplined, faithful, pious to God, and responsible (cf. Exodus 20:12; Ephesians 6:1-3; Colossians 3:20). This study uses a qualitative method. Qualitative research methods are methods for investigating and interpreting humanitarian problems by involving questions, data collection mechanisms, identifying and analyzing field data and interpreting the findings descriptively. The findings are that the process of character formation of students at Nehemia Galela Christian High School is through classroom learning with Christian religious subjects, giving advice and motivation in morning and afternoon assemblies, giving students assignments to make worship journals, student council worship, choosing inspiring memorization verses, and watching spiritual videos. The obstacles experienced in the formation of student character are the lack of cooperation between teachers and parents, internal and external influences. So it can be concluded that learning tools, school equipment and strategies are neat and ideal both nationally and internally but there is no cooperation between teachers and parents and no moral awareness of students then the formation of student character which is the goal of the school will be in vain and will not succeed.   Tujuan penelitian ini adalah menganalisis pembentukan karakter siswa di SMA Kristen Nehemia Galela, dan menganalisis PAK Sebagai Pendekatan dalam membentukan karakter siswa di SMA Kristen Nehemia Galela di digital agar siswa memiliki karakter Kristen yakni cerdas, peduli, bermartabat, disiplin rohani, beriman, bertaqwa kepada Tuhan, dan bertanggung jawab (bdk. Keluaran 20:12; Efesus 6:1-3; Kolose 3: 20). Penelitian ini menggunakan metode kualitatif karena menyelidiki dan memaknai masalah kemanusian dengan melibatkan pertanyaan, mekanisme mengumpulkan data, mengidentifikasi dan menganalisis data lapangan dan menginterpretasi hasil temuan secara deskriptif. Hasil temuannya adalah bahwa proses pembentukan karakter siswa di SMA Kristen Nehemia Galela adalah melalui pembelajaran kelas dengan mata pelajaran agama Kristen, memberi nasihat dan motivasi dalam apel pagi dan siang, memberi tugas kepada siswa membuat jurnal ibadah, ibadah osis, memilih ayat hafalan yang menginspirasi, dan menonton video rohani. Kendala yang dialami dalam pembentukan karakter siswa adalah tidak ada kerja sama antara guru dengan orang tua, pengaruh internal dan eksternal. Maka dapat disimpulkan bahwa perangkat pembelajaran, perangkat sekolah dan  strategi yang rapih dan ideal baik secara nasional maupun internal sekolah tapi tidak ada kerja sama antara guru dan orang tua dan tidak ada kesadaran moral siswa maka pembentukan karakter siswa yang adalah tujuan sekolah menjadi sia-sia dan tidak akan berhasil.